Essentials of evangelical theology ; v. 2 - Bloesch, Donald G., 1928- (San Francisco, CA Harper and Row, 1978)
Contents : v. 2 : Life, ministry and hope. Includes bibliographical references and indexes.
Keywords: Evangelicalism -- theology